SCREEN CULTURE VS BOOK CULTURE: PERSPECTIVES OF DIALOGUE / ЭКРАННАЯ КУЛЬТУРА VS КНИЖНАЯ КУЛЬТУРА: ПЕРСПЕКТИВЫ ДИАЛОГА - KONDAKOV I.V. / КОНДАКОВ И.В. (Наука телевидения, 2016)
The article deals with the interaction of on-screen and book texts, where texts in screen form are able to detect implicit deep structure of visual texts, the key to which are precisely the verbal texts. On-screen text (visual and verbal) designed for a single, one-time perception; book texts initially assume re-reading. As a result of interaction with the screen a literary text acquires the sub-media space, with its uncertain status and mysterious semantics.